2022
DOI: 10.3390/ijerph19159590
|View full text |Cite
|
Sign up to set email alerts
|

Adapted Physical Activity Protocol for Lower Limb Functional and Strength Recovery in a Young Athlete with Cutaneous Melanoma: Feasibility and Efficacy during COVID-19 Pandemic

Abstract: Adapted physical activity (APA) can improve psychophysical wellbeing and quality of life (QoL) in cancer survivors, a vulnerable population requiring a global management, especially during the recent pandemic. On this basis, we investigated for the first time the impact of a tailored APA intervention on a melanoma-affected 18-year-old female athlete to counteract treatment sequelae and promote lower limb functional and strength recovery. Patient was evaluated at baseline and post-protocol by a test battery foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 49 publications
0
0
0
Order By: Relevance
“…Even though leisure and sport activities specifically addressing this vulnerable target population are more oriented to overall psychophysical well-being recovery than to performance [108], in the case of stabilized outcomes, sport-specific athletic training and mixed strength-resistance exercise benefits have been demonstrated over time [33,[109][110][111]. Supervised progressive exercise plays a crucial role in correcting/mitigating treatment-related postural alterations and muscle recruitment imbalance, hence helping to prevent injuries and upper body morbidity exacerbation [40,81]. Particularly, proprioceptive exercises targeted to this anatomofunctional region can effectively re-educate sensorimotor patterns and postural awareness by enhancing muscle flexibility, joint stability, and neuromuscular coordination [91,112,113].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though leisure and sport activities specifically addressing this vulnerable target population are more oriented to overall psychophysical well-being recovery than to performance [108], in the case of stabilized outcomes, sport-specific athletic training and mixed strength-resistance exercise benefits have been demonstrated over time [33,[109][110][111]. Supervised progressive exercise plays a crucial role in correcting/mitigating treatment-related postural alterations and muscle recruitment imbalance, hence helping to prevent injuries and upper body morbidity exacerbation [40,81]. Particularly, proprioceptive exercises targeted to this anatomofunctional region can effectively re-educate sensorimotor patterns and postural awareness by enhancing muscle flexibility, joint stability, and neuromuscular coordination [91,112,113].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the literature has widely demonstrated that the recent pandemic and the consequent anti-contagion restrictions led to a drastic change in lifestyle behaviors, thus causing a massive physical fitness decline in all ages of the global population [121,122]. Several studies highlighted that these confinement-related detraining issues have been even worse and hard to counteract when referred to a vulnerable target such as oncological individuals [81,123]. Though gradually resumed, dragon boat training might simply have evidenced this phenomenon particularly referred to the anatomical regions most involved in paddling-specific motor gestures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation